Analysis of vitexin in aqueous extracts and commercial products of Andean Passiflora species by UHPLC-DAD - Paula Sepúlveda, Geison M. Costa, Diana Marcela Aragón, Freddy Ramos, Leonardo Castellanos (Journal of Applied Pharmaceutical Science, 2018)
Plants of the Passiflora genus are extensively cultivated in South America, as their edible fruits are widely commercialized. They are also recognized worldwide for their ethnopharmacological uses. Different Pharmacopoeias indicate vitexin as the chemical marker for P. incarnata, the most widely studied Passiflora species worldwide. In the present work, some species of Passiflora from the Andean region of Colombia and commercial phytotherapeutic products were evaluated for their vitexin content by UHPLC-DAD. From the studied species: ‘banana passion fruits’ (P. tripartita var tripartita, P. tripartita var mollissima, P. mixta, P. cumbalensis, P. tarminiana), ‘passion fruits’ (P. edulis var flavicarpa, P. edulis var edulis), ‘granadillas’, (P. ligularis, P. quadrangularis) and ‘sweet passion fruit’ (P. alata), the aqueous extracts of P. mixta, P. tripartita var mollissima and P. edulis var edulis showed quantifiable amounts of vitexin (4.58 ± 1.23; 2.49 ± 0.2; 0.3 ± 0.0 mg g−1 dry extract, respectively). Additionally, four of the six botanical phytotherapeutic products tested showed considerable quantities of this flavonoid. The results obtained suggest that vitexin cannot be used as the only chemical marker for the quality control of the studied Passiflora species.
Keywords: Passiflora,vitexin,flavonoids,UHPLC,quality control.